The influence of foreign direct investment inflows on economic growth in Nigeria - Olorunsola E. Olowofeso; Isaiah O. Ajibola; Offioig D. Orenowo (West African Journal of Monetary and Economic Integration, 2021)
This paper investigates the connection between foreign direct investment and economic growth in Nigeria during the period 2000Q1-2020Q2 using an Autoregressive Distributed lag model. We control for the influence of several macroeconomic variables, including treasury bill rate, government expenditure and trade openness. The bounds cointegration test confirms a long run relationship between economic growth and the included variables. Our results show that foreign direct investment impacts positively on economic growth in the long run, albeit insignificantly. These results are robust to alternative sample size and the inclusion of additional variables that represent alternative investment outlets for non-residents, such as portfolio investment (PFI) and OMO bills. Our results highlight the need for the promotion of an investment-friendly environment as a way of boosting foreign direct investment and sustaining economic growth in Nigeria.
Keywords: 330